Variation of Dynamic Elasticity Modulus with Experimentally Determined Concrete Compressive Strength - Tugrul, Esra (My University, 2023)
In reinforced concrete structures, one of the most important factors for structural safety is the quality of concrete. The first thing that comes to mind for concrete quality is the compressive strength of concrete. However, properties such as elasticity modulus are also among the properties that determine concrete quality. Since concrete is a brittle material, different methods are used to determine dynamic elasticity modulus. In practice, dynamic elasticity modulus of concrete can be identified by utilizing concrete compressive strength value. In this context; compressive strength tests were performed on a series of concretes accordingly relevant standards. Since it is difficult to determine elasticity modulus from the stress and strain relationship, the dynamic elasticity modulus values in this study was calculated using empirical formulas according to TS 500-2000, ACI 318-95 and CEB-FIP 1978 on the basis of experimental data in this study. The relationship between the calculated dynamic elasticity modulus values and concrete compressive strength was analyzed. From the study, it is concluded that as concrete compressive strength increases, dynamic elasticity modulus increases for the concrete specimens.
Keywords: Compressive strength; concrete specimens; dynamic elasticity modulus; concrete quality